Pengaruh Pengetahuan Keuangan, Sikap Keuangan, Dan Locus Of Control Terhadap Perilaku Pengeolaan Keuangan Mahasiswa Manajemen FEB UPGRIS: Studi Kasus Pada Mahasiswa FEB UPGRIS Angkatan 2017-2019 - Dewi Una Sari (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
This study aims to determine the effect of financial knowledge, financial attitudes, and locus of control on the behavior of management students at the Faculty of Economics and Business, PGRI University Semarang. This type of research is quantitative, the population of this study are students of Management. This study used a stratified random sampling technique with a sample size of 239 people. The results of this study indicate that there is a positive and significant influence between financial knowledge on financial management behavior with an influence level of 37.6%, there is a positive and significant influence between financial attitudes on financial management behavior with an influence level of 35%, there is a positive and significant influence. between locus of control on financial management behavior with a level of influence of 52%, financial knowledge, financial attitudes and locus of control have a simultaneous effect on financial management behavior. The results of testing the coefficient of determination obtained a value of the Adjusted R Square of 0.577 which can be concluded that financial knowledge, financial attitudes and locus of control simultaneously affect the financial management behavior of Management students of the Faculty of Economics and Business by 57.7% while the remaining 41.7% is influenced by other variables not studied.